08. Calculando a expressão abaixo obtemos:
2.(1/2-1/3:(1/2-1/6)²
a) 3 b) c d) 2 e) n.d.a.
AminIs:
Ja respondi
Respostas
respondido por:
3
Resposta:
d) 3/2
Explicação passo-a-passo:
(1/2 - 1/3) : (1/2 - 1/6)²
Vamos separar em 2 partes:
1a -> (1/2 - 1/3) => (3/6 - 2/6) => 1/6
2a -> (1/2 - 1/6)² => (3/6 - 1/6)² => (2/6)² => (1/3)² => 1/9
Juntando tudo novamente temos => (1/6)/(1/9) => (9/6) => 3/2 ou 1,5
Perguntas similares
4 anos atrás
4 anos atrás
6 anos atrás
6 anos atrás
6 anos atrás
8 anos atrás